Multiparametric magnetic resonance imaging in diagnosis of long‐term renal atrophy and fibrosis after ischemia reperfusion induced acute kidney injury in mice. (27th June 2022) - Wang, Feng; Otsuka, Tadashi; Adelnia, Fatemeh; Takahashi, Keiko; Delgado, Rachel; Harkins, Kevin D.; Zu, Zhongliang; de Caestecker, Mark P.; Harris, Raymond C.; Gore, John C.; Takahashi, Takamune
Abstract : Tubular atrophy and fibrosis are pathological changes that determine the prognosis of kidney disease induced by acute kidney injury (AKI). We aimed to evaluate multiple magnetic resonance imaging (MRI) parameters, including pool size ratio (PSR) from quantitative magnetization transfer, relaxation rates, and measures from spin‐lock imaging ( R 1 ρ and S ρ ), for assessing the pathological changes associated with AKI‐induced kidney disease. Eight‐week‐old male C57BL/6 J mice first underwent unilateral ischemia reperfusion injury (IRI) induced by reperfusion after 45 min of ischemia. They were imaged using a 7T MRI system 56 days after the injury. Paraffin tissue sections were stained using Masson trichrome and picrosirius red to identify histopathological changes such as tubular atrophy and fibrosis. Histology detected extensive tubular atrophy and moderate fibrosis in the cortex and outer stripe of the outer medulla (CR + OSOM) and more prominent fibrosis in the inner stripe of the outer medulla (ISOM) of IRI kidneys. In the CR + OSOM region, evident decreases in PSR, R 1, R 2, R 1 ρ, and S ρ showed in IRI compared with contralateral kidneys, with PSR and S ρ exhibiting the most significant changes. In addition, the exchange parameter S ρ dropped by the largest degree among all the MRI parameters, while R 2 * increased significantly. In the ISOM of IRI kidneys, PSR increased while S ρ kept decreasing. R 2, R 1 ρ, and R 2 * all increased due to more severe fibrosis in this region. Among MRI measures, PSR and R 1 ρ showed the highest detectability of renal changes no matter whether tubular atrophy or fibrosis dominated. R 2 * and S ρ could be more specific to a single pathological event than other MRI measures because only R 2 * increased and S ρ decreased consistently when either fibrosis or tubular atrophy dominated, and their correlations with fibrosis scores were higher than other MRI measures. Multiparametric MRI may enable a more comprehensive analysis of histopathological changes following AKI. Abstract : Tubular atrophy and fibrosis are pathological changes that determine the prognosis of kidney disease induced by acute kidney injury (AKI). We aimed to evaluate multiple MRI parameters, including pool size ratio (PSR) from quantitative magnetization transfer, relaxation rates, and measures from spin‐lock dispersion imaging, for assessing long‐term changes after AKI.